Hippocampal neurochemicals are associated with exercise group and intensity, psychological health, and general cognition in older adults - Line S. Reitlo; Jelena M. Mihailovic; Dorthe Stensvold; Ulrik Wisløff; Fahmeed Hyder; Asta Kristine Håberg (GeroScience, 2023)
Based on the premise that physical activity/exercise impacts hippocampal structure and function, we investigated if hippocampal metabolites for neuronal viability and cell membrane density (i.e., N-acetyl aspartate (NAA), choline (Cho), creatine (Cr)) were higher in older adults performing supervised exercise compared to following national physical activity guidelines. Sixty-three participants (75.3 ± 1.9 years after 3 years of intervention) recruited from the Generation 100 study (NCT01666340_date:08.16.2012) were randomized into a supervised exercise group (SEG) performing twice weekly moderate- to high-intensity training, and a control group (CG) following national physical activity guidelines of ≥ 30-min moderate physical activity ≥ 5 days/week. Hippocampal body and head volumes and NAA, Cho, and Cr levels were acquired at 3T with magnetic resonance imaging and spectroscopic imaging. Sociodemographic data, peak oxygen uptake (VO 2peak ), exercise characteristics, psychological health, and cognition were recorded. General linear models were used to assess group differences and associations corrected for age, sex, education, and hippocampal volume. Both groups adhered to their training, where SEG trained at higher intensity. SEG had significantly lower NAA/Cr in hippocampal body than CG ( p = 0.04). Across participants, higher training intensity was associated with lower Cho/Cr in hippocampal body ( p < 0.001). Change in VO 2peak , increasing VO 2peak from baseline to 3 years, or VO 2peak at 3 years were not associated with hippocampal neurochemicals. Lower NAA/Cr in hippocampal body was associated with poorer psychological health and slightly higher cognitive scores. Thus, following the national physical activity guidelines and not training at the highest intensity level were associated with the best neurochemical profile in the hippocampus at 3 years.